2018
DOI: 10.1039/c8sc01638k
|View full text |Cite
|
Sign up to set email alerts
|

Pyrene hydrogel for promoting direct bioelectrochemistry: ATP-independent electroenzymatic reduction of N2

Abstract: We demonstrate a novel hydrogel material to facilitate direct bioelectrochemistry of a wide range of redox proteins and enable ATP-independent electroenzymatic reduction of N2 by nitrogenase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 64 publications
(88 citation statements)
references
References 39 publications
1
84
0
3
Order By: Relevance
“…Several studies have shown that photocatalytically generated electrons can be transferred to the MoFe protein of nitrogenase, thus allowing N 2 to NH 3 without the need for the Fe protein and ATP hydrolysis. [ 10b,58 ] King et al used cadmium sulfide (CdS) nanocrystals to photosensitize the MoFe protein, where electron transfer from the conduction band of CdS to the MoFe protein efficiently drove enzymatic ammonia synthesis. [ 10b ] Such bio‐photocatalysis systems allow exploitation of both photoexcited charge carrier transfer of semiconductors and the precise active sites of nitrogenase, providing a rich toolbox to improve the efficiency of ammonia synthesis under ambient conditions.…”
Section: Key Developments In Low‐temperature Nitrogen Fixationmentioning
confidence: 99%
“…Several studies have shown that photocatalytically generated electrons can be transferred to the MoFe protein of nitrogenase, thus allowing N 2 to NH 3 without the need for the Fe protein and ATP hydrolysis. [ 10b,58 ] King et al used cadmium sulfide (CdS) nanocrystals to photosensitize the MoFe protein, where electron transfer from the conduction band of CdS to the MoFe protein efficiently drove enzymatic ammonia synthesis. [ 10b ] Such bio‐photocatalysis systems allow exploitation of both photoexcited charge carrier transfer of semiconductors and the precise active sites of nitrogenase, providing a rich toolbox to improve the efficiency of ammonia synthesis under ambient conditions.…”
Section: Key Developments In Low‐temperature Nitrogen Fixationmentioning
confidence: 99%
“…In order to achieve this, a novel polymer functionalized with pyrene was employed. It is reported that these studies are able to achieve N 2 fixation independent of the Fe protein and ATP‐hydrolysis, representing a new prospect for N 2 fixation by nitrogenase . However, much work is required to fully exploit MoFe protein catalysis in this system.…”
Section: Recent Examples Of Enzymatic Electrochemistry For Small Molementioning
confidence: 99%
“…Hickey et al. developed a pyrene modified linear polyethyleneimine, which promotes protein adsorption and direct electron transfer of laccase and other proteins . For instance, this polymer was used in square wave voltammetric studies to determine the redox potentials of the cofactor and the P cluster in MoFe nitrogenase, VFe nitrogenase, and FeFe nitrogenase .…”
Section: Thermodynamicsmentioning
confidence: 99%